Talent management as a mechanism for retention and sustainable performance - Najma Zahira; Abd. Rasyid Syamsuri (PT Aksara Indo Rajawali, 2026)
Purpose – This article aims to analyse how talent management is associated with employee performance, retention, job satisfaction, and organizational sustainability, while also identifying the mechanisms that explain variations in prior findings. Design/methodology/approach – This study employed a systematic literature review approach supported by conceptual synthesis. The literature search was conducted using Publish or Perish, while duplicate removal and screening were supported by Covidence. Microsoft Excel was used to map the selected studies based on author, year, context, method, outcome, and key findings. A total of 14 articles published between 2020 and 2026 met the inclusion criteria and were analysed. Findings – The synthesis revealed that talent management contributes to organizational outcomes through three interrelated pathways. The first is the psychological pathway, in which talent management practices strengthen employee engagement, thriving at work, job satisfaction, and employee voice. The second is the capability pathway, in which talent management supports innovation, resilience, agility, and competitive advantage. The third is the sustainability pathway, in which talent management encourages sustainable behaviour and process innovation, thereby contributing to sustainable organizational performance. Research limitations – This study is limited to 14 selected articles, which means that the findings should not be generalized to all organizational contexts without further empirical validation. Implications – The findings suggest that organizations should design talent management policies beyond recruitment and retention by strengthening learning and development, career management, succession planning, employee voice, and process innovation. Originality – This article synthesizes fragmented talent management literature into an integrated strategic human resource management framework that explains how talent management creates value for retention and sustainable performance.